3x-7=2(x+4)+x-1

Simple and best practice solution for 3x-7=2(x+4)+x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-7=2(x+4)+x-1 equation:



3x-7=2(x+4)+x-1
We move all terms to the left:
3x-7-(2(x+4)+x-1)=0
We calculate terms in parentheses: -(2(x+4)+x-1), so:
2(x+4)+x-1
We add all the numbers together, and all the variables
x+2(x+4)-1
We multiply parentheses
x+2x+8-1
We add all the numbers together, and all the variables
3x+7
Back to the equation:
-(3x+7)
We get rid of parentheses
3x-3x-7-7=0
We add all the numbers together, and all the variables
-14!=0
There is no solution for this equation

See similar equations:

| 19-6p=-41 | | 79-(-5x-6)0=245x+336 | | 22-2f=6 | | 3(x+1)=2x+4+x-1 | | 2q-8q+9=-8q-9 | | 4v=-68 | | -3(x-1)=-(2x-2)-x+1 | | -6u=-7-7u | | 62+94=77x+70-40x | | -9+2+p=5-p | | -155=-5(1+6a) | | Y=1/11x+9 | | 24=-8b+2b | | w+1.7=9.13 | | 3(6x-3)=10x+7 | | 2y+3(y+5)=6y | | 7x+0.8=7.8 | | 10-12(1-x)=8(-12-6x)-14 | | F=3x-0,5 | | -7m+10=-5m-10 | | 3x-7-2x=2x-4x+4 | | 7s=8s-10 | | F=3x-½ | | 3a-a+23=-13 | | 2x+8=185 | | -4+8c=9c | | -175=-5(7+4a) | | -d-10=8+5d | | -d−10=8+5d | | F(x)=3x-½ | | 7x+26=-30 | | 3a-9+23=-13 |

Equations solver categories